Investigation into the Effect of Spinel Pigments on the Photostability and Combustion Properties of Ethylene-Norbornene Copolymer - Kuśmierek, Małgorzata (Materials (Basel), 2021)
Multicolor ethylene-norbornene (EN) composites filled with three different spinel pigments (Cobalt Green-PG50, Zinc Iron Yellow-PY 119, Praseodym Yellow-PY159) were prepared by melt mixing and characterized in terms of their stability under destructive environmental conditions. The EN films were subjected to accelerated aging by ultraviolet (UV) photooxidation for 300 h, 600 h, or 900 h. The mechanical performance of the EN composites was investigated in static and dynamic mechanical tests. The morphologies of the EN samples and their color changes during the aging process were evaluated by scanning electron microscopy (SEM) and spectrophotometric measurements. Fourier transform infrared (FTIR) spectroscopy was applied to determine the amount of carbonyl groups resulting from surface oxidation at different aging times. The effects of the spinel pigments on the thermal stability and combustion properties of the multicolor polymer composites were also assessed, and compared with a sample containing the organic Pigment Yellow 139 (PY139). The results show that the color changes (ΔE) in the spinel pigments were minor in comparison to those in the organic pigment (PY139) and the reference film. The Zinc Yellow (PY119) pigment was the most effective stabilizer of EN copolymer. Moreover, the spinel pigments had a positive effect on the flame retardancy of the EN composites. Microcombustion tests (MCC) showed that the incorporation of both the spinels and the organic pigment PY139 into the EN matrix reduced the heat release rate (HRR) and total heat release (THR) parameters.